EVALUASI SUPPLIER OBAT DI PUSKESMAS XYZ DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Noor Nailie Azzat, Nor Helmi Handayani, Gunawan Mohammad, (Universitas Muria Kudus, 2023)
The problem with the XYZ Health Center is the slow delivery of goods and claims that are not handled properly and quickly, the number of items that are not in accordance with orders causes the availability of drug stock to become empty. Therefore, it is necessary to set standards in the selection of suppliers by determining the criteria and sub-criteria according to the policy of the Puskesmas in selecting suppliers to supply drug stock availability at the XYZ Puskesmas. The main objective of this research is to find the best supplier ranking according to the criteria and sub-criteria. The research uses the Analytical Hierarchy Process (AHP) method in decision making and expert choice software in processing the data from the questionnaire results. The research results obtained 5 criteria with 15 sub-criteria in selecting suppliers. The quality criteria with a weight of 0,2998 and the drug reliability sub-criteria with a weight of 0,1227 are the criteria and sub-criteria with the highest weighting results. Based on the ranking using the AHP method, PT A is an alternative supplier with the highest weight value, namely 0,2042 and a percentage of 20%, it can be concluded that PT A is the best supplier to be maintained.